2022
DOI: 10.1111/ahe.12873
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis of the skull of Hamdani sheep via Three‐Dimensional modelling

Abstract: The aim of the present study was to determine the craniometric characteristics of the crania of Hamdani sheep, one of local breeds of Turkey, by using computed tomography (CT). In the study, 13 (six female and seven male) skulls were used. After CT images of the skulls were taken, their three‐dimensional models were created by MIMICS 20.1 (The Materialise Group, Leuven, Belgium) program. Thirty‐eight craniometric measurements were taken over the models created and nine indices were calculated by using these me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Dayan et al. ( 2022 ) detected the greatest breadth of the foramen magnum parameter as 20.48 ± 0.64 mm in males and 20.77 ± 0.60 mm in females in their study on Hamdani sheep, while Parés‐Casanova et al. reported the same parameter as 20.00 ± 2.00 mm in a study conducted on Rasquera White goats in 2014.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Dayan et al. ( 2022 ) detected the greatest breadth of the foramen magnum parameter as 20.48 ± 0.64 mm in males and 20.77 ± 0.60 mm in females in their study on Hamdani sheep, while Parés‐Casanova et al. reported the same parameter as 20.00 ± 2.00 mm in a study conducted on Rasquera White goats in 2014.…”
Section: Discussionmentioning
confidence: 91%
“…Dayan et al. ( 2022 ) reported the greatest length of nasals parameter as 83.66 ± 3.23 mm in males and 82.99 ± 3.11 mm in females, while Dalga et al. ( 2018 ) reported it as 82.51 ± 7.89 mm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Choudhary, Prıyanka, Kalıta, et al (2020), a study on Mizoram goats, reported the CL result as 9.10 ± 0.03 cm. In addition, CL value in the 3D modelling study performed on Hamdani sheep skulls, was determined as 125.49 ± 2.84 mm in males and 121.40 ± 1.94 mm in females (Dayan et al, 2023).…”
Section: Discussionmentioning
confidence: 99%